A blade cutter design for an effective oil palm fronds cuting process - Mohd Zain Abdullah@Join Gorob (2023)
This study aimed to design an improved crosscut blade for fronds cutting in the oil palm industry, considering the cutting vector X-Y-Z axis and testing different blade designs based on various Kerf-Sets tooth trigonometrical patterns. The research consisted of two stages; the development of a statistical laboratory test rig platform to analyze the cutting timeline in the Straight-Tooth sections, and a High Accelerated Life Test (HALT) conducted in real field conditions to assess reliability and tooth fracture-wear. The results showed that blade type "F" met the technical design requirements, achieving a Hardness Rockwell of 127HRC per 1mm2. The N14TP14 Kerf-Sets tooth size provided the fastest fronds cutting, powered by 100V, with a recorded timeline of 00:15.7 seconds per 6.5 kg pressing drag mass cutting against 29 cm2 fresh fronds specimens. These findings contribute to the development of an improved crosscut blade design, with blade type "F" N14TP14 tooth configuration being the most effective, exhibiting high Hardness Rockwell and no fractured tooth blades. The large Kerf-Set tooth sizing facilitated strong cutting force, and the correct Pitch Pressure Angle design Type B at Cosine 100 to 150 contributed to prolonged sharpness quality.